Pengembangan Modul Pembelajaran Berbasis Pmri Pada Materi Operasi Hitung Perkalian Dan Pembagian Kelas IV SD - Erni*, Erni; Rohana, Rohana; Fakhrudin, Ali (Universitas Negeri Makassar, 2022)
The purpose of this study is to develop a learning module based on the Indonesian Realistic Mathematics Education (PMRI) approach to the material for multiplication and division operations in grade IV elementary school that is valid and practical. This type of research is Research and Development (R&D). This study uses the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were fourth-grade students at SD Negeri 89 Palembang. Data collection techniques used are questionnaires and documentation. The validation process was carried out by 3 experts, namely material experts, media experts, and linguists with an average of 92.5% categorized as very valid. The level of practicality after being tested on students and educators got an average score of 94% so it was categorized as very practical. Thus, it can be concluded that the learning module based on the Indonesian Realistic Mathematics Education (PMRI) approach that has been developed is very valid and very practical.